Whole Genome Sequencing and Root Colonization Studies Reveal Novel Insights in the Biocontrol Potential and Growth Promotion by Bacillus subtilis MBI 600 on Cucumber - Samaras, Anastasios; Nikolaidis, Marios; Antequera-Gómez, Maria Luisa; Cámara-Almirón, Jesus; Romero, Diego; Moschakis, Thomas; Amoutzias, Grigoris D.; Karaoglanidis, Georgios S. (Frontiers in Microbiology, 2021)
Bacillus spp. MBI 600 is a gram-positive bacterium and is characterized as a PGPR strain involved in plant growth promoting and control of various plant pathogens that has recently been introduced into the agricultural practice. In this study we performed a Next Generation Sequencing analysis, to analyze the full genome of the microorganism and to characterize it taxonomically. Results showed that MBI 600 strain was phylogenetically close to other Bacillus spp. strains used as biocontrol agents and identified as B. subtilis. GOG analysis showed clusters contributed to secondary metabolites production such as fengycin and surfactin. In addition, various genes which annotated according to other plant-associated strains, showed that play a main role in nutrient availability from soil. The root colonization ability of MBI 600 strain was analyzed in vivo with a green fluorescence protein (yfp) tag. Confocal laser scanning microscopy of cucumber roots treated with yfp-tagged MBI 600 cells, revealed that the strain exhibits a strong colonization ability of cucumber roots, although it is affected significantly by the growth substrate of the roots. In vitro and in planta experiments with MBI 600 strain and F. oxysporum f.sp radicis cucumerinum and P. aphanidernatum, showed a high control ability against these soilborne pathogens. Overall, our study demonstrates the effectiveness of MBI 600 in plant growth promotion and antagonism against different pathogens, highlighting the use of this microorganism as a biocontrol agent.